Blockchains in operations and supply chains : a model and reference implementation - Helo, Petri; Hao, Yuqiuge (Elsevier, 2019)
Blockchain is a promising information technology which can provide several potential applications related to operations and supply chains. By using distributed software architecture and advanced computing, blockchain can solve the problem of immutable ledgers distributed to several actors in the chain. This paper reviews blockchain technology and outlines possible uses for immutable distributed ledgers in operations and supply chains. A classification of the applications of blockchain technology in the scope of operations and supply chain management is presented. In order to demonstrate the technical architecture of the blockchain-based logistics monitoring system (BLMS), a reference implementation was programmed and tested based on Ethereum. The purpose of the BLMS is to provide a solution for parcel tracking in a supply chain to support an open and immutable history record for each transaction. The functionality of the system consists of transaction entry for logistics operators. The presented reference architecture demonstrates how blockchain can be implemented in the operations and supply chain context by using software components.
Keywords: Blockchain; Distributed ledger; Operations; Supply chain; Logistics; fi=Tuotantotalous (TkK)|en=Industrial Management and Engineering|